Taxonomic and ecological studies of vascular plants at entrances of selected caves in Polillo Island, Quezon, Philiipines - Hadsall, Annalee S.; Cariño, Grace Angelique F.; Lambio, Ivy Amor F.; Cajano, Mary Ann O.; Larona, Ariel R.; Lit, Ireneo L., Jr. (2011)
Partial results of on-going taxonomic survey and ecological studies of vascular plants found t entrances of caves on Polillo Island, Quezon, Philippines are presented. This is the first study that specifically focuses on cave entrance plants in the Philippines. The limited availability of light in cave environments consequently limits primary productivity therein. Hence, photosynthetic organisms are found mainly at the entrances and to a very limited extent, in the twilight zones of caves. Photographs were taken for documentation and common or familiar plants were identified during field surveys. Samples of uncommon as well as unidentified species were collected, brought and preserved for further study and verification at the Botanical and Forestry Herbaria of the UPLB Museum of Natural History. Species include hoyas, begonias, several aroids, ferns, palms, strangling figs, urticaceous plants, etc. Several are known lithophytes whereas a few are also known as invasive or weedy. The taxonomic list of these plants is very important as baseline information for biodiversity and conservation of Philippine caves.
Keywords: Caves; Polillo Island (Quezon); Plants